Business and Marketing Mix Analysis of Bacang Food Industry Through Conventional and Online Marketing (Case: El Shaddai Food Small Industry) - Dyah Aring Hepiana Lestari; Ktut Murniati; Evelyn Faviana (School of Business, Bogor Agricultural University (SB-IPB), 2021)
Bacang agroindustry is undeveloped in Indonesia and the internet has not been maximally utilized by bacang entrepreneurs. Therefore, business and marketing analysis of bacang agroindustry is important to do to develop the business and internet utilization for bacang agroindustry. The research aims to analyze profit, cost of goods manufactured, financial performance, marketing mix, and the impact of online marketing on the chicken bacang agroindustry. This research uses a case study method at El Shaddai Food Agroindustry, Penjaringan District, North Jakarta. Research data were collected from December 2019 until February 2020 and the data analysis methods used were qualitative and quantitative descriptive analysis. The results showed that conventional marketing profit was smaller than online marketing profit and the selling price exceeded the cost of goods manufactured, so the agroindustry was considered viable on every marketing method. Financial performance in the last three years was quite good. The marketing mix was not good. Online marketing gave an impact on agroindustry revenue and profit. Keywords: agroindustry, bacang, business, marketing mix, online